Closed reduction and percutaneous pinning for treatment of unstable lateral condyle fractures of the humerus in children - Qiao, Fei; Guan, Xiaohong; Jiang, Fei; Lv, Ping (Frontiers in Pediatrics, 2023)
In the past, obviously displaced lateral condyle fractures of the humerus in children were treated satisfactorily with open reduction and internal fixation (ORIF). However, in recent years, more studies have mentioned closed reduction and percutaneous pinning (CRPP) of these fractures. In this retrospective investigation, the radiographic and clinical results of patients with these fractures that were initially managed with CRPP were newly classified. We classified these fractures into three groups according to the degree and pattern of fracture displacement as identified on four radiographic images. In Type Ⅰ, the fracture is unstable and displacement is ≥ 2 mm; In Type Ⅱ degree Ⅰ, the fracture is unstable and displacement is ＞2 mm，with single rotation of fragment; In Type Ⅱ degree Ⅱ, the fracture is unstable and displacement is ＞2 mm，with single rotation of fragment，with rotation of fragment and antero-proximal displacement; In Type Ⅲ, the fracture is unstable and displacement is ＞ 2 mm ， with posterior dislocation of elbow joint. We also designed an algorithm for closed reduction of these fractures according to this new classification. We retrospectively analyzed the radiographic and clinical results of 37 unstable fractures (in 22 boys and 15 girls) that were treated with closed reduction. Twenty-one of 25 (84.0%) type Ⅰ fractures, which could have been reduced to within 2 mm of residual displacement, were treated with closed reduction and pinning with 2 or 3 Kirschner wires (K wires). Three of 5 (60.0%) type Ⅱ degree Ⅰ, 3 of 4 (75.0%) type Ⅱ degree Ⅱ, and 3 of 3 (100%) type Ⅲ fractures were treated with CRPP. In 4 of 25(16.0%) type Ⅰ, 2 of 5 (40.0%) type Ⅱ degree Ⅰ and 1 of 4 (25.0%) type Ⅱ degree Ⅱ fractures, closed reduction failed, so ORIF was implemented.This retrospective study showed that type III fractures should not be ignored as a lateral condyle fracture that can be cured with CRPP and that lateral humeral condyle fractures with obvious displacement and rotation can be initially treated with CRPP to achieve satisfactory recovery of the elbow. Kirschner wire (K wire) fixation is recommended.